Oportunistas, falsarios … Reflexiones sobre la actitud religiosa de la aristocracia en el s. IV d.C. - Enjuto Sánchez, Begoña (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Julian’s 79th letter is a good example of the ideological and religious conflict which the aristocracy was living in the end of 4th century. Focusing on Pegasus’ bishop charges, first by apostate later as “lapsus”, the analyses of this document shows us the controversial and complex process of the making of a Christian aristocracy, especially in the oriental Roman Empire area.